Creative Economy as an Alternative Solution to Increase Competitiveness in the Digital Era - Syairozi, Muhamad Imam; Rozaini, Rozaini; Susanti, Ike (Journal of International Conference Proceedings, 2023)
The rapid development of information and communication technology is currently able to encourage the growth of business activities entering the era of creative economy to be very elastic and dynamic in facing the challenges of globalization and modernization. This study uses a qualitative descriptive approach with a literature study method. The results of the analysis state that the creative economy is a manifestation of efforts to find a formula for sustainable development through ideas and creativity. The creative economy is an alternative solution to the welfare of society in improving the economy to become competitive.